Research progress on extraction technology and biomedical function of natural sugar substitutes - Lei, Pengyu; Chen, Haojie; Ma, Jiahui; Fang, Yimen; Qu, Linkai; Yang, Qinsi; Peng, Bo; Zhang, Xingxing; Jin, Libo; Sun, Da (Frontiers in Nutrition, 2022)
Improved human material living standards have resulted in a continuous increase in the rate of obesity caused by excessive sugar intake. Consequently, the number of diabetic patients has skyrocketed, not only resulting in a global health problem but also causing huge medical pressure on the government. Limiting sugar intake is a serious problem in many countries worldwide. To this end, the market for sugar substitute products, such as artificial sweeteners and natural sugar substitutes (NSS), has begun to rapidly grow. In contrast to controversial artificial sweeteners, NSS, which are linked to health concepts, have received particular attention. This review focuses on the extraction technology and biomedical function of NSS, with a view of generating insights to improve extraction for its large-scale application. Further, we highlight research progress in the use of NSS as food for special medical purpose (FSMP) for patients.